Implementasi Manajemen Kurikulum dan Pembelajaran Muatan Lokal Pada Mts Negeri 32 Jakarta - Supendi Supendi; Asep Abdul Wadud; Hanafiah Hanafiah (Peneliti.net, 2023)
The purpose of this research is to analyze the implementation of the special local content learning curriculum implemented at MTs Negeri 32 Jakarta. The research method used is descriptive qualitative method. The results of the study show that the process of planning the local content learning curriculum for the Islamic boarding school program at MTSN 32 Jakarta includes the vision, mission and goals of education. The organization of the local content learning curriculum at MTSN 32 Jakarta is divided into two groups, namely general science and religion, the national curriculum and local content. The implementation of the local content learning curriculum for the Islamic boarding school program enters school hours. While the implementation in the teacher's class carries out by making prota, promissory notes, promissory notes, syllabus, and lesson plans. The implementation of local content learning for the Islamic boarding school program at MTSN 32 Jakarta for delivery uses lecture and practice methods. Evaluation of the local content learning curriculum for the Islamic boarding school program at MTSN 32 Jakarta conducts evaluations in the form of written tests, practice tests and rote tests which are conducted once a month, every semester and at the end of each lesson